Hemiorchis rhodorrhachis Schum. (Zingiberaceae) - A new record for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2005)
Not available. Key words: Hemiorchis rhodorrhachis, new record, Bangladesh DOI: 10.3329/bjpt.v12i1.613 Bangladesh J. Plant Taxon. 12(1): 59-61, 2005 (June)